The Relationship Between Emotional Intelligence And Adolescent Religiusity In Students Of SMA Negeri 2 Medan - Ahmad Khan, Hafiz; Amanah , Surbakti; Salamiah Sari , Dewi (International Journal of Science, Technology & Management, 2023)
Abstract School is a determining factor for the development of a child's (student) personality, both in the way of thinking, behaving, and how to behave. Many problems (juvenile delinquency) arise in the process of adaptation and interaction between adolescents and their environment. The purpose of this study was to determine the relationship between emotional intelligence and religiosity together with juvenile delinquency in students of SMA Negeri 2 Medan. This study used a quantitative research method with a correlational approach with a sample of 208 teenagers. The results showed that there was a negative relationship between emotional intelligence and juvenile delinquency as seen from the value of the coefficient (rxy) = -0.777 with p = 0.000 <0.050, meaning that there was a negative relationship between emotional intelligence and juvenile delinquency. The higher the emotional intelligence, the lower the delinquency. teenager.